A wavelet analysis for exploring the relationship between economic policy uncertainty and tourist footfalls in the USA. Issue 15 (14th September 2019) - Singh, Ritu; Das, Debojyoti; Jana, R. K.; Tiwari, Aviral Kumar
ABSTRACT: We attempt to establish the relationship between Economic Policy Uncertainty (EPU) and international tourist footfalls in the USA. In the first stage, we investigate the influence of country-specific EPU and global EPU on tourist footfalls. Since, these two are overlapping in nature, in the second stage, we study the isolated influence of country-specific EPU on footfalls by eliminating the influence of global EPU and vice versa. We consider a study period spanning over January 1997 to April 2017. To capture the variations in the relationship at different time dimensions, we apply wavelet-based techniques. We observe the following: (a) the impact of policy uncertainty shock has a little immediate impact on tourist footfalls, (b) medium to long-run shocks persist due to occurrence of major undesirable economic events, and (c) the influence of domestic (country-specific) EPU is dominant in comparison to global EPU for the USA.